A Policy Framework for the Digital Library - Ubogu, Felix (My University, 2013)
The paper argues that it is essential that an institution has an appropriate policy framework in place in order to ensure the long-term success of its digital library programme and that institutions do not have to reinvent the wheel but can adapt policies already in use by other institutions. Information gathered on digital libraries and repositories shows that many repositories do not have appropriate policies with regard to Content, Preservation, Metadata Re-use and Data Re-use. A comparison of the policies also shows a wide degree of variation, particularly in terms of depth and breadth of coverage. In South Africa, most institutions confirmed that they either had no policy or were in the process of drafting one.
Digital libraries and repositories
Keywords: A Policy Framework.